Match each function with the corresponding function formula when h(x) = 2 – 2x and g(x) = –2 x + 2.

1.
k(x) = (h – 2g)(x)
2.
k(x) = (g + h)(x)
3.
k(x) = (h – g)(x)
4.
k(x) = (2g + h)(x)
5.
k(x) = (g – h)(x)
6.
k(x) = (2h – 2g)(x)

Respuesta :

the correct functions are

h(x) = 3x + 2

g(x) = 2^x

proceed to calculate the different values ​​of K (x)

case 1) k(x) = g(x) ∘ h(x)

g(x) ∘ h(x)=g(h(x))

k(x) = [2]^[3x + 2]-----------> is the option 4. k(x) = 2^(3x + 2 )

case 2) k(x) = g(x) + h(x)

k(x) = [2^x]+[3x + 2]=2^x+3x+2--------> is the option 1.) k(x) = 2^x + 3x + 4


case 3)k(x) = g(x) - h(x)

k(x) = [2^x]-[3x + 2]=2^x-3x-2--------> is the option 2.) k(x) = 2^x - 3x - 2